Efforts to Improve Poetry Writing Abilities by Implementing The Educational Game "Words Connect" for Students of SDN 06 Rantau Utara Labuhan Ratu Regency - Derianna Rambe, Anna; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
This research is motivated by initial observations that indicate that sixth-grade students still experience difficulties in writing poetry, especially in word choice, use of figures of speech, and understanding the structure of poetry. This research was conducted at SDN 06 Rantau Utara, Labuhan Batu Regency in the 2025-2026 academic year. The research subjects were sixth-grade students. The research instruments used included observation sheets to observe student activities during learning and poetry writing skills tests (pre-test and post-test) to measure the improvement of students' poetry writing abilities. Data collection techniques used were observation, tests, and documentation of student work. Data were analyzed quantitatively and qualitatively. Quantitative analysis was carried out by comparing the average pre-test and post-test scores and the percentage of student completion in each cycle. Qualitative analysis was carried out by analyzing the results of observations and documentation to determine the processes and obstacles faced by students during learning. The results showed that the implementation of the "Sambung Kata" game can improve the poetry writing abilities of sixth-grade students at SDN 06 Rantau Utara. Quantitatively, there was an increase in the average poetry writing test score from cycle to cycle. This increase was also seen in the percentage of students who achieved learning completion. In cycle I, the percentage of students who completed was only 25%, but increased to 85% in cycle II. Qualitatively, the results of observations showed that students were more active and enthusiastic in participating in poetry writing learning after the implementation of the "Sambung Kata" game. They also appeared more creative in choosing words and using figures of speech in their poems. This game proved effective in improving students' vocabulary and word choice, which ultimately had an impact on improving poetry writing skills